World Development Report 2018 : Learning to Realize Education's Promise - World Bank (Washington, DC: World Bank, 2017)
Every year, the World Bank's World Development Report takes on a topic of central importance to global development. The 2018 Report, Learning to Realize Education's Promise, is the first ever devoted entirely to education. Now is an excellent time for it: education has long been critical for human welfare, but is even more so in a time of rapid economic change.